Manipulation of self-assembled three-dimensional architecture in reusable acoustofluidic device - Nguyen, Tan Dai (2022)
Reconstructing of cell architecture plays a vital role in tissue engineering. Recent developments of self-assembling of cells into three-dimensional (3D) matrix pattern using surface acoustic waves have paved a way for a better tissue engineering platform thanks to its unique properties such as nature of noninvasive and noncontact, high biocompatibility, low-power consumption, automation capability, and fast actuation. This article discloses a method to manipulate the orientation and curvature of 3D matrix pattern by redesigning the top wall of microfluidic chamber and the technique to create a 3D longitudinal pattern along preinserted polydimethylsiloxane (PDMS) rods. Experimental results showed a good agreement with model predictions. This research can actively contribute to the development of better organs-on-chips platforms with capability of controlling cell architecture and density. Meanwhile, the 3D longitudinal pattern is suitable for self-assembling of microvasculatures.